NMR and experimental reinvestigation of the condensation reaction between γ-methylene-α, β-unsaturated aldehydes and propargyl aldehydes. Issue 9 (8th February 2018) - Riveira, Martín J.; Sarotti, Ariel M.
Abstract : An experimental and computational study of the reaction between γ-methylene enals and propargyl aldehydes uncovered a deconjugative aldol condensation. Abstract : The condensation reaction between a γ-methylene-α, β-unsaturated aldehyde and phenylpropargyl aldehyde was revisited and, guided by extensive DFT calculations of NMR shifts, was found to afford a deconjugative aldol condensation product. In this manner, a simple protocol for the preparation of valuable cross -conjugated oxatrienes was uncovered.